2023
DOI: 10.3390/molecules28073004
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Omega-3 Supplementation against Doxorubicin-Induced Deleterious Effects on the Liver and Kidneys of Rats

Abstract: Anthracycline doxorubicin (DOX) is still widely used as a chemotherapeutic drug for some solid tumors. Although DOX is highly effective, its side effects are limiting factors, such as cardio, nephro and hepatotoxicity. As such, approaches used to mitigate these adverse effects are highly encouraged. Omega 3 (ω-3), which is a class of long-chain polyunsaturated fatty acids, has been shown to have anti-inflammatory and antioxidant effects in preclinical bioassays. Thus, we evaluated the protective effects of ω-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…However, these histological alterations in the hepatic structures were dramatically restored in the rats that were concomitantly treated with DOX/AALE, which exhibited an improvement in the hepatic architectures, represented by regular central vein, fewer congestions, and less cellular infiltrations, implying protection from DOX-induced hepatic damage. These findings are in line with previous studies that reported the ameliorative effects of natural products against DOX-induced hepatotoxicity in rats [50][51][52].…”
Section: Discussionsupporting
confidence: 93%
“…However, these histological alterations in the hepatic structures were dramatically restored in the rats that were concomitantly treated with DOX/AALE, which exhibited an improvement in the hepatic architectures, represented by regular central vein, fewer congestions, and less cellular infiltrations, implying protection from DOX-induced hepatic damage. These findings are in line with previous studies that reported the ameliorative effects of natural products against DOX-induced hepatotoxicity in rats [50][51][52].…”
Section: Discussionsupporting
confidence: 93%